Hubungan Komunikasi Perawat Dengan Tingkat Kepuasan Tentang Pelayanan Kesehatan Pada Pasien Tuberculosis Paru Di Puskesmas Sukodono Sidoarjo - Devi Dwi Indriyanti (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2012)
Nurse communication is information delivery in an interaction face to face that contain an idea, caring and thinking that is given nurse to patient. Nurse communication is done in every nurse care to satisfy patient but some of them feel not satisfy with the health services because the feel its not optimally. The purpose of this research is to know correlation between nurse communication and the level of satisfaction about health services among lungs tuberculosis patients in Puskesmas Sukodono. Design of this research is cross sectional, the number of samples counted 34 respondents and its done by purposive sampling technique. Independent variable is nurse communication, dependent variable is the level satisfaction of health service among lung tuberculosis patients. Based from communication that was done by nurse in verbal communication gotten that 28 respondents (82.4%) said good, and in non verbal communication gotten that 13 respondents (38.2%) said enough. In the level of satisfaction of health service found that 21 respondents (61.8%) said satisfied to the health services in Puskesmas Sukodono. These data was collected by questioner and observational and then analyzed by statistical test of Spearman's rho with significant of Pvalue < 0.05.The result of this research show that there are correlation between nurse communication and the level of satisfaction about health services among lung tuberculosis (Pvalue = 0.000). Based from the research can be made conclusion that there are correlation between nurse communication and the level of satisfaction about heath service among lung tuberculosis in Puskesmas Sukodono. And to reduce and to and to prevent from un satisfy of lung tuberculosis patient in Puskesmas Sukodono so the nurses hoped to follow workshops about communication for health services.